2012
DOI: 10.1097/qai.0b013e31824330cb
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Abnormality in HIV-Infected Children and Adolescents Living in Europe

Abstract: Fat abnormality was prevalent in close to half of children and adolescents, who had accumulated long treatment durations. Risk of fat abnormality was associated with specific drugs, including stavudine and ritonavir, and other variables. Our results underline the importance of continued surveillance of children treated with antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 63 publications
2
54
1
6
Order By: Relevance
“…A recent cohort study of European children reported that nearly half had signs of fat redistribution and nearly a quarter had an abnormal lipid profile 103. Risk factors included advanced HIV disease, and use of d4T, NNRTIs, PIs and triple‐class ART.…”
Section: Drug Toxicities and Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent cohort study of European children reported that nearly half had signs of fat redistribution and nearly a quarter had an abnormal lipid profile 103. Risk factors included advanced HIV disease, and use of d4T, NNRTIs, PIs and triple‐class ART.…”
Section: Drug Toxicities and Interactionsmentioning
confidence: 99%
“…This should be borne in mind when considering which drug to use in children with established psychological/neurological disturbance. Other complications associated with EFV are dyslipidaemia, abnormal fat distribution 103 and gynaecomastia.…”
Section: Drug Toxicities and Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, metabolic abnormalities were found in 34% to 42% of children which is comparable to our study. [12][13][14][15][16][17] In our study significant number of children developed LDS and FR when ART was initiated below 5 years of age as compared to older age. A similar correlation was not found among the children who developed metabolic abnormality.…”
Section: Discussionmentioning
confidence: 91%
“…Recent data from the Pediatric European Network for the Treatment of AIDS group suggests that children starting ART at 10 years of age are less likely to ever achieve a normal CD4 count, and that this reduction might have long-term consequences [1]. A cross-sectional study of 426 HIV-positive adolescents in Europe found that around 57% had lipodystrophy syndrome (blood lipid and body fat abnormalities) [2]. HIV-infected children and adolescents also have increased levels of biomarkers associated with obesity, insulin resistance and atherosclerotic cardiovascular disease risk in adults [3].…”
Section: Complications Of Hiv Therapy In Children and Adolescentsmentioning
confidence: 99%